PERAN FINANCIAL DISTRESS MEMEDIASI PENGARUH RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN - Silvia Restycha Dewi; Anisa Putri (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2024)
ABSTRACT This study aims to analyze the role of financial distress in mediating the effect of financial ratios on firm value. The dependent variable in this study is profitability, liquidity and solvency, while the independent variable is the value of the company with financial distress as the intervening variable. The research method used is causal comparative by using secondary data in the form of company financial statements. The sample in the study was selected using the purposive sampling method, so that a sample of 54 was obtained from 18 industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019- 2021 period. The data was processed using SPSS version 26. The test results in this study indicate that profitability and financial distress have no effect on firm value, while liquidity and solvency have an effect on firm value. Profitability, liquidity, and solvency have no effect on financial distress. Based on the Sobel test, it shows that financial distress is not able to mediate the effect of profitability, liquidity, and solvency on firm value. Keywords: Financial distress, financial ratios, profitability, liquidity, solvency, firm value